2018
DOI: 10.1021/acs.est.7b05211
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene Nanoplastics-Enhanced Contaminant Transport: Role of Irreversible Adsorption in Glassy Polymeric Domain

Abstract: Nanoplastics (NPs) are becoming an emerging pollutant of global concern. A potential risk is that NPs may serve as carriers to increase the spreading of coexisting contaminants. In this study, we examined the effects of polystyrene nanoplastics (PSNPs, 100 nm), used as a model NP, on the transport of five organic contaminants of different polarity in saturated soil. The presence of low concentrations of PSNPs significantly enhanced the transport of nonpolar (pyrene) and weakly polar (2,2',4,4'-tetrabromodiphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(78 citation statements)
references
References 58 publications
4
73
0
1
Order By: Relevance
“…Nonetheless, the role of MPs as vectors of contaminants still presents contradictory interpretations [124,125]: while some ecotoxicological studies have determined that plastic can have a synergic effect with respect to pollutants (e.g., [120,126,127]), other studies have reported negligible changes in contaminant uptake in the presence of MPs (e.g., [128][129][130]).…”
Section: Interaction Of Mps With Micropollutantsmentioning
confidence: 99%
“…Nonetheless, the role of MPs as vectors of contaminants still presents contradictory interpretations [124,125]: while some ecotoxicological studies have determined that plastic can have a synergic effect with respect to pollutants (e.g., [120,126,127]), other studies have reported negligible changes in contaminant uptake in the presence of MPs (e.g., [128][129][130]).…”
Section: Interaction Of Mps With Micropollutantsmentioning
confidence: 99%
“…Because of the strong sorption affinity to organic contaminants, NPs/MPs can act as carriers to migrate together with pollutants in the environment. Liu et al [71] reported that PS NPs can significantly enhance the transport of the nonpolar contaminants Pyr and polar 2,2 ,4,4 -tetrabromodiphenyl ether at low concentrations (5-20 mg/L); however, it had little effect on three polar compounds, bisphenol A, bisphenol F, and 4-nonylphenol. This is likely because desorption hysteresis on NPs occurs only in nonpolar/weakly polar contaminants.…”
Section: Effect Of Nps/mps On Organic Contaminant Transportmentioning
confidence: 99%
“…Nanoplastics are known to have a higher surface area/volume ratio than MP. Thus, increasing interactions with persistent organic pollutants (POP) (Liu et al, 2018;Velzeboer et al, 2014) and biological membranes (Rossi et al, 2014) calling for an accurate description of NP in the context of the chemical/biological risks in aquatic systems (Koelmans et al, 2016;Paul-Pont et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%